2014
DOI: 10.5603/kp.a2014.0072
|View full text |Cite
|
Sign up to set email alerts
|

Impact of serum alkaline phosphatase level on the pathophysiologic mechanism of contrast-induced nephropathy

Abstract: CIN was observed in 20.5% of patients. Advanced age, male gender, elevated creatinine, uric acid and phosphate levels, and low glomerular filtration rate were correlated with the development of CIN. Correlation analysis also showed a significant association between the ALP level and the development of CIN (126.1 ± 144.9 vs. 97.2 ± 46.9, p = 0.004). Univariate regression analysis also showed the impact of ALP on the development of CIN (OR 1.004, 95% CI 1.001–1.007, p = 0.02). Conclusions: Our outcomes indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…In previous studies [5,6], we reported that hyperuricemia was an independent risk factor for CI-AKI in PCI patients, which was consistent with other studies [7][8][9][10][11][12]. However, other studies did not show the same conclusion [13,14] [17]. However, even though they reported that high SUA was an independent predictor of CI-AKI in STEMI patients, there was no uniform standard for the definition of hyperuricemia.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In previous studies [5,6], we reported that hyperuricemia was an independent risk factor for CI-AKI in PCI patients, which was consistent with other studies [7][8][9][10][11][12]. However, other studies did not show the same conclusion [13,14] [17]. However, even though they reported that high SUA was an independent predictor of CI-AKI in STEMI patients, there was no uniform standard for the definition of hyperuricemia.…”
Section: Discussionsupporting
confidence: 79%
“…In previous studies, we reported that hyperuricemia was an independent risk factor for CI-AKI after PCI [5,6]. However, the conclusion remains controversial [7][8][9][10][11][12][13][14]. In addition, only a limited number of studies reported that hyperuricemia was an independent predictor of CI-AKI in STEMI patients undergoing pPCI.…”
Section: Introductionmentioning
confidence: 97%
“…The universal term AKI may be more appropriate than CI-AKI in this clinical setting. Novel markers of renal dysfunction might bring additional information about the mechanisms and prognosis of kidney injury and provide its earlier detection [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies did not show the same conclusion 13,14 . Several studies explored the effect of serum uric acid (SUA) on CI-AKI among risk high-risk patients such as STEMI undergoing primary PCI.…”
Section: Discussionmentioning
confidence: 81%